Analysis of Factors Affecting the Profitability of Islamic Rural Banks in Indonesia: A Dynamic Regression Model Approach - Nano Prawoto (Publisher Cv. Inara Colaboration with www.stie-sampit.ac.id, 2026)
This study aims to examine the factors affecting the profitability of Islamic Rural Banks (BPR Syariah) in Indonesia using a dynamic regression model. The data employed are monthly observations from January 2020 to December 2025, totaling 72 observations. The variables analyzed include profit as the main dependent variable, as well as cash, profit-sharing financing, mudharabah financing, murabahah financing, assets, and lagged profit. All variables are transformed into logarithmic form and estimated using the Ordinary Least Squares (OLS) method. The results indicate that, collectively, all variables have a significant effect on profitability. Individually, profit-sharing financing and lagged profit exhibit a positive and significant influence, implying that increases in these factors lead to higher profitability. In contrast, assets show a negative and significant effect, suggesting that asset growth is not necessarily accompanied by an increase in profit. Cash has a positive effect, while mudharabah financing shows a negative effect at a more lenient significance level. Meanwhile, murabahah financing does not have a significant impact on profitability. The Adjusted R-squared value indicates that the model explains approximately 41.4% of the variation in profitability, while the remaining portion is influenced by other factors not included in the model. Overall, these findings highlight the importance of effective financing management and asset efficiency in improving the profitability performance of Islamic Rural Banks.